La malédiction du catéchiste - Franck Beuvier (Socio-anthropologie, 2018)
The introduction of indigenous catechists would constitute the armed wing of evangelization in Cameroon and the Bamileke chiefdoms. Recruited to fill the benches of the Christian school, children and adolescents represented for the missionaries the future indigenous cadres of the new Church. At the beginning of the 1910s, the first catechists formed an emergent category, which, very quickly, proved to be the pivot of Christian life. Promoted as representatives of the religious order of whites and as mediators between the people and the missionaries, they had a duty to preach the doctrine by opposing local morals and customs. The biography of the catechist Bernard Ngou here serves as a guiding thread, and reveals an impossible destiny in these early times: a life guided by an attachment to Christian precepts and punctuated by unusual or unfortunate circumstances, in which the suspicion of witchcraft was never dispelled. The path of the cross which dominates this narrative sketches a specifically Bamileke motif of Christian persecution.